Pengaruh Cyberbullying terdahap Absensi Siswa Sekolah Dasar - Asmoro, Fajar Ayu; Sari, Fani Lia; Putri, Anggi Aprilia; Mustika, Putri; Setyowati, Sri Agus (Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This study aims to investigate the effect of cyberbullying on elementary school students' absenteeism levels. Cyberbullying is an increasingly disturbing phenomenon in the digital world, and its impact on children's well-being is not yet fully understood. In this study, we conducted a survey and data analysis of elementary school students to evaluate the extent to which cyberbullying experiences contributed to their absenteeism. The results of this research will provide deeper insight into the impact of cyberbullying on student absenteeism rates, which can be used as a basis for the development of more effective intervention and protection strategies in basic education environments.